Impact of a Homeless Encampment Closure on Crime Complaints in the Bronx, New York City, 2017: Implications for Municipal Policy. Issue 3 (4th May 2022) - Allen, Bennett; Nolan, Michelle L.
ABSTRACT: Purpose: As part of COVID-19 control policy, the Centers for Disease Control and Prevention has advised local jurisdictions to permit the formation of homeless encampments to prevent community disease spread. This new federal public health guidance is in conflict with existing police policies in many jurisdictions to raze or evict homeless encampments upon discovery. However, no empirical research on homeless encampment policy actions exists. Methods: This study utilized interrupted time series to estimate the impact of the 2017 closure of "the Hole"—a longstanding encampment of homeless people who use drugs in the Bronx, New York City—on crime complaints. Daily crime complaints originating from public spaces within 1 mile of the encampment were captured during the 30-day periods before and after closure. Results: Closure was associated with no short-term changes in complaints [IRR=1.01; 95% CI (0.81-1.27)], with daily complaints remaining at baseline levels during the post-closure period [IRR 0.99; 95% CI (0.98-1.00)]. Discussion: Findings preliminarily suggest that the presence of a homeless encampment may not have been associated with increased levels of crime in the neighborhood where it was located. Future research is necessary to understand the health and social impacts of homeless encampments and inform municipal policymakers.